CREASE: Synchronous gait by minimizing actuation through folded geometry. (December 2020) - Mesa, Olga; Mhatre, Saurabh; Aukes, Dan
The Age of the Fourth Industrial Revolution promises the integration and synergy of disciplines to arrive at meaningful and comprehensive solutions. As computation and fabrication methods become pervasive, they present platforms for communication. Value exists in diverse disciplines bringing their approach to a common conversation, proposing demands, and potentials in response to entrenched challenges. Robotics has expanded recently as computational analysis, and digital fabrication methods are more accurate and reliable. Advances in functional microelectromechanical components have resulted in the design of new robots presenting alternatives to traditional ambulatory robots. However, most examples are the result of intense computational analysis necessitating engineering expertise and specialized manufacturing. Accessible fabrication methods like laminate techniques propose alternatives to new robot morphologies. However, most examples remain overly actuated without harnessing the full potential of folds for locomotion. Our research explores the connection between origami structures and kinematics for the generation of an ambulatory robot presenting efficient, controlled, and graceful gait with minimal use of components. Our robot 'Crease' achieves complex gait by harnessing kinematic origami chains rather than relying on motors. Minimal actuation activates the folds to produce variations in walk and direction. Integrating a physical iterative process with computational analysis, several prototypes were generated at different scales, including untethered ones with sensing and steering that could map their environment. Furthering the dialogue between disciplines, this research contributes not only to the field of robotics but also architectural design, where efficiency, adjustability, and ease of fabrication are critical in designing kinetic elements.